Extraordinary encounters : authenticity and the interview - Smith, Katherine, 1979-; Staples, James, 1966-; Rapport, Nigel, 1956- (Methodology and history in anthropology ;, 2015)
Given the anthropological focus on ethnography as a kind of deep immersion, the interview poses theoretical and methodological challenges for the discipline. This volume explores those challenges and argues that the interview should be seen as a special, productive site of ethnographic encounter, a site of a very particular and important kind of knowing. In a range of social contexts and cultural settings, contributors show how the interview is experienced and imagined as a kind of space within which personal, biographic and social cues and norms can be explored and interrogated. The intervie.